Game LoP: Fostering Logical-Mathematical Intelligence in Early Childhood - Wulansari, Widi; Wati, Epritha Kurnia (Jurnal Pendidikan Anak Usia Dini Undiksha, 2024)
Logical-mathematical intelligence is one of the essential skills that early childhood must develop to support their future educational journey. However, many children are reluctant to learn logical mathematics as it is often perceived as difficult to understand. To address this issue, an educational medium in the form of an educational game is needed to attract children's interest in learning logical mathematics. This study aims to evaluate the effectiveness of the educational media Game LoP in enhancing early childhood logical-mathematical skills. The research employs a quasi-experimental design involving pretest-post-test and control group comparisons. Research instruments include pretest and post-test assessments analyzed using paired t-tests and independent t-tests. The findings reveal a significant difference in early logical-mathematical abilities between the control and experimental groups following the implementation of Game LoP. Additionally, there was a notable improvement in the logical-mathematical abilities of children using this educational medium. Therefore, Game LoP has been proven to yield positive and significant outcomes in enhancing early childhood logical-mathematical skills. This study implies that the application of Game LoP can serve as an innovative solution to support the development of children's logical-mathematical intelligence.